Defective NOD2 peptidoglycan sensing promotes diet‐induced inflammation, dysbiosis, and insulin resistance. Issue 3 (9th February 2015) - Denou, Emmanuel; Lolmède, Karine; Garidou, Lucile; Pomie, Celine; Chabo, Chantal; Lau, Trevor C; Fullerton, Morgan D; Nigro, Giulia; Zakaroff‐Girard, Alexia; Luche, Elodie; Garret, Céline; Serino, Matteo; et al.
Abstract Pattern recognition receptors link metabolite and bacteria‐derived inflammation to insulin resistance during obesity. We demonstrate that NOD2 detection of bacterial cell wall peptidoglycan (PGN) regulates metabolic inflammation and insulin sensitivity. An obesity‐promoting high‐fat diet (HFD) increased NOD2 in hepatocytes and adipocytes, and NOD2−/− mice have increased adipose tissue and liver inflammation and exacerbated insulin resistance during a HFD. This effect is independent of altered adiposity or NOD2 in hematopoietic‐derived immune cells. Instead, increased metabolic inflammation and insulin resistance in NOD2−/− mice is associated with increased commensal bacterial translocation from the gut into adipose tissue and liver. An intact PGN‐NOD2 sensing system regulated gut mucosal bacterial colonization and a metabolic tissue dysbiosis that is a potential trigger for increased metabolic inflammation and insulin resistance. Gut dysbiosis in HFD‐fed NOD2−/− mice is an independent and transmissible factor that contributes to metabolic inflammation and insulin resistance when transferred to WT, germ‐free mice. These findings warrant scrutiny of bacterial component detection, dysbiosis, and protective immune responses in the links between inflammatory gut and metabolic diseases, including diabetes.